Scala Cookbook, 2nd Edition - Alexander, Alvin (O'Reilly Media, Inc., 2021)
Save time and trouble building object-oriented, functional, and concurrent applications with Scala 3. The latest edition of this comprehensive cookbook is packed with more than 250 ready-to-use recipes and 700 code examples to help you solve the most common problems when working with Scala and its popular libraries. Whether you're working on web, big data, or distributed applications, this cookbook provides recipes based on real-world scenarios for experienced Scala developers and for programmers just learning to use this JVM language. Author Alvin Alexander includes practical solutions from his experience using Scala for highly scalable applications that support concurrency and distribution. Recipes cover: Strings, numbers, and control structures Classes, methods, objects, traits, packaging, and imports Functional programming in a variety of situations Building Scala applications with sbt Collections covering Scala's wealth of classes and methods Actors and concurrency List, array, map, set, and more Files, processes, and command-line tasks Web services and interacting with Java Databases and persistence, data types and idioms.